MeCP2 SUMOylation rescues Mecp2-mutant-induced behavioural deficits in a mouse model of Rett syndrome - Derek J. C. Tai (Nature Portfolio, 2016)
Post-translational modifications of methyl-CpG-binding protein 2 (MeCP2) are important for its function and dysfunction in Rett syndrome. Here, Tai et al. show a functional interaction between MeCP2 SUMOylation and phosphorylation in rodent behavior and synaptic plasticity.